Polishing slurry and polishing method

By using C2-C20 amine compounds and organic phosphonic acid and other components in the polishing slurry, the damage to cobalt and polishing surface defects of existing polishing slurry is solved, and rapid removal of cobalt and high-quality polishing is achieved.

CN119490793APending Publication Date: 2025-02-21HUAWEI TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311052019.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When the existing polishing slurry polishes, it will cause damage to the cobalt or cause more defects in the polishing surface, and the removal rate selection ratio is not suitable.

Method used

A polishing slurry including solvents, abrasives, stabilizers, complexing agents and corrosion inhibitors are used, wherein the complexing agent is an amine compound of C2-C20 and the corrosion inhibitor is an organic phosphonic acid. Through the combination of these components, the Cobalt removal rate and optimize removal rate selection ratio.

Benefits of technology

The rapid removal of cobalt is achieved, while ensuring the surface quality after polishing, reducing surface roughness and defects, and achieving a more reasonable removal rate selection ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490793A_ABST
    Figure CN119490793A_ABST
Patent Text Reader

Abstract

The invention provides polishing slurry and a polishing method. The polishing slurry comprises a solvent, and an abrasive, a stabilizer, a complexing agent and a corrosion inhibitor which are dispersed in the solvent, the complexing agent can be an amine compound with C2-C20, the amine compound contains at least two amino groups, and the mass ratio of the complexing agent in the polishing slurry can be 0.05%-0.2%; the corrosion inhibitor can be organic phosphonic acid, and the organic phosphonic acid is selected from at least one of phosphonic carboxylic acid or hydroxyethylidene-1, 1-diphosphonic acid; and the mass ratio of the corrosion inhibitor in the polishing slurry can be 0.005%-0.04%. By means of the polishing slurry, the removal rate of cobalt in a chip can be increased, the removal rate selection ratio is high, and a good polished surface is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of chip polishing, and in particular to a polishing slurry and a polishing method. Background Art

[0002] With the miniaturization and increasing complexity of semiconductor devices, the manufacture of nanoelectronic devices requires increasingly complex multilayer wiring processes. In the multilayer wiring process, due to the reduction in the size of the circuit board, the width of the metal routing in the circuit board is also getting smaller and smaller. At present, the characteristic size of the chip can be reduced to below 10nm. At this time, the metal line width gradually approaches the electron mean free path of Cu, and the resistivity of Cu will increase sharply, resulting in more serious resistance (resistance, R)-capacitance (capacitance, C) delay in the interconnection circuit. Compared with Cu, Co has a lower mean free path and can effectively replace W in the middle process and Cu in the back process at low technology nodes to avoid the deterioration of RC delay caused by the reduction in chip size. In the process of chip preparation, polishing slurry is usually used to chemically mechanically polish the surface of the chip to flatten the chip. The existing polishing slurry is generally a polishing slurry developed for copper. When Co is polished using this type of polishing slurry, it will cause certain damage to Co, or there will be more polishing surface defects due to the incompatibility of the removal rate selection ratio of Co and the barrier layer. Summary of the invention

[0003] The present application provides a polishing slurry and a polishing method to improve the removal rate of cobalt in a chip and a high removal rate selectivity, and obtain a good polishing surface.

[0004] In the first aspect, the present application provides a polishing slurry, which includes a solvent and an abrasive, a stabilizer, a chelating agent and a corrosion inhibitor dispersed in the solvent; the chelating agent may be an amine compound having C2-C20, and the amine compound contains at least two amino groups; the mass proportion of the chelating agent in the polishing slurry may be 0.05% to 0.2%; the corrosion inhibitor may be an organic phosphonic acid, and the organic phosphonic acid is selected from at least one of phosphinoylic acid or hydroxyethylene diphosphonic acid; the mass proportion of the corrosion inhibitor in the polishing slurry may be 0.005% to 0.04%.

[0005] The polishing slurry of the present application uses an amine compound as a complexing agent to increase the removal rate of Co. The removal rate of Co can be The above. Using organic phosphonic acid as a corrosion inhibitor can slow down the static corrosion rate of Co by the polishing slurry, effectively ensuring the surface quality of Co after polishing; at the same time, it can slow down the removal rate of the protective layer and the barrier layer by the polishing slurry, so that the protective layer and the protective layer have a lower removal rate. Therefore, the polishing slurry of the present application can achieve a more reasonable removal rate selection ratio while achieving high-speed removal of Co. After polishing, the surface roughness of Co can be reduced to about 1.0, reducing surface defects.

[0006] In an optional implementation, the amine compound as a complexing agent may contain 2-6 amine groups. In an optional implementation, the amine compound may be selected from at least one of ethylenediamine, ethylenediaminetetraacetic acid, diethyltriaminepentaacetic acid, dipotassium ethylenediaminetetraacetic acid and disodium ethylenediaminetetraacetic acid. Preferably, the amine compound is ethylenediaminetetraacetic acid. By using ethylenediaminetetraacetic acid as a complexing agent, the rapid removal of cobalt is achieved by utilizing its special chelating structure.

[0007] In an optional implementation, the organic phosphonic acid is selected from phosphinocarboxylic acids.

[0008] In an optional implementation, the complexing agent is ethylenediaminetetraacetic acid, and the organic phosphonic acid is phosphine carboxylic acid. In an optional implementation, the complexing agent is ethylenediaminetetraacetic acid, and the organic phosphonic acid is hydroxyethylene diphosphonic acid.

[0009] In an optional implementation, the polishing slurry further includes a surfactant, which may be a nonionic surfactant. By selecting a nonionic surfactant, the introduction of additional impurity ions can be avoided, and the aggregation of large particles in the polishing slurry can be avoided.

[0010] Exemplarily, the nonionic surfactant can be selected from at least one of emulsified silicone oil, high carbon alcohol fatty acid ester complex, polyoxyethylene, polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether, polyoxypropylene polyoxyethylene glycerol ether and polydimethylsiloxane.

[0011] In an optional implementation, the polishing slurry further includes at least one of a defoaming agent, a bactericide and a pH adjuster.

[0012] The defoamer may be selected from at least one of a polydimethylsiloxane defoamer, an organosilicon defoamer and a polyether organosilicon defoamer.

[0013] The bactericide can be selected from at least one of dodecyl dimethyl benzyl ammonium chloride, dodecyl dimethyl benzyl ammonium bromide, tetradecyl dimethyl benzyl ammonium chloride, polyquaternium salt, isothiazolinone, benzisothiazolinone and glutaraldehyde. The pH regulator can be selected from at least one of potassium hydroxide, sodium hydroxide, tetramethyl ammonium hydroxide, tetraethyl ammonium hydroxide, ammonia water, nitric acid, hydrochloric acid, HEDP, sulfuric acid and its derivatives.

[0014] In an optional implementation, the stabilizer may be selected from at least one of hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, hydroxyethyl methyl cellulose and benzyl cellulose.

[0015] In addition, the polishing slurry may further include an oxidant. For example, the oxidant may be selected from hydrogen peroxide. The solvent in the present application may be an aqueous solvent, such as deionized water.

[0016] In an optional implementation, the polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent and 0.05-0.4 parts of corrosion inhibitor, and the remainder is solvent.

[0017] In an optional implementation, the polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent, 0.05-0.4 parts of corrosion inhibitor, 0.01-0.03 parts of nonionic surfactant, and the remainder is solvent.

[0018] In an optional implementation, the polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent and 0.05-0.4 parts of corrosion inhibitor, 0.01-0.03 parts of non-ionic surfactant, 0.004-0.006 parts of defoamer, 0.005-0.02 parts of bactericide and pH regulator and the remaining solvent. The pH value of the polishing slurry is 2-12. The amount of pH regulator can be added according to the target pH value.

[0019] In an optional implementation, the polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent and 0.05-0.4 parts of corrosion inhibitor, 0.01-0.03 parts of non-ionic surfactant, 0.004-0.006 parts of defoamer, 0.01-0.03 parts of bactericide, 3-5 parts of oxidant and pH regulator and the rest of solvent. The pH value of the polishing slurry is 2-12. The amount of pH regulator can be added according to the target pH value.

[0020] In a second aspect, the present application provides a method for polishing a substrate, comprising the following steps: applying the polishing slurry in the first aspect of the present application and any optional implementation method to the surface of the substrate, and driving the polishing object to polish the surface of the substrate covered with the polishing slurry; wherein the substrate includes a metal area, and the surface of the metal area is in contact with the polishing slurry.

[0021] The polishing method of the present application uses the polishing slurry of the present application to polish the substrate. During the polishing process, the complexing agent chelates with the metal in the metal area of ​​the substrate, such as true chelation of Co metal, and the Co metal can be quickly removed. At the same time, due to the presence of the corrosion inhibitor, rapid corrosion of the oxide layer and the barrier layer is avoided, and excessive corrosion holes are not generated on the corrosion surface, so as to form a surface with a good surface roughness, thereby improving the surface quality of the substrate.

[0022] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the content and proportion of each component in the polishing slurry, when measuring, the values ​​within the engineering measurement error range should be understood to be within the range specified in the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of a chemical polishing process of a wafer containing a Co metal layer according to an embodiment;

[0024] Figure 2 The micro-light morphology images of samples of different embodiments and comparative examples after chemical mechanical polishing;

[0025] Figure 3 The effect of different concentrations (0.01wt.%, 0.03wt.%, 0.05wt.%, 0.07wt.%, 0.1wt.%) of PBTCA on Co removal rate;

[0026] Figure 4 The effect of different concentrations (0.01wt.%, 0.03wt.%, 0.05wt.%, 0.07wt.%, 0.1wt.%) of PBTCA on the removal rate of TiN and oxide layer;

[0027] Figure 5 The effect of different concentrations (0.01wt.%, 0.03wt.%, 0.05wt.%, 0.07wt.%, 0.1wt.%) of PBTCA on the Co / oxide layer removal rate selectivity;

[0028] Figure 6 The effect of different concentrations (0%, 0.03wt.%, 0.1wt.%) of PBTCA on the surface quality of Co after polishing;

[0029] Figure 7The effects of different concentrations (0%, 0.03wt.%) of PBTCA on TiN and Oxide surfaces;

[0030] Figure 8 and Fig. 9 The relationship between the step change of different line widths and PBTCA after chemical mechanical polishing;

[0031] Fig.10 This is the surface morphology of the cobalt-coated film after polishing under a laser confocal microscope.

[0032] Figure Number:

[0033] 11-Co metal layer; 12-barrier layer. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.

[0035] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0036] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0037] The chip usually includes a substrate and a metal layer buried in the substrate, and part of the surface of the metal layer can leak out of the substrate. The surface of the substrate can be provided with an oxide layer as a protective layer. The oxide layer can be silicon dioxide or a metal oxide. In addition, a barrier layer, such as a TaN layer, can be provided between the metal layer and the substrate. As the feature size of the chip decreases, Cu in the advanced node can be replaced by Co. As Co is gradually introduced into the chip, it is necessary to develop a polishing slurry for Co metal to achieve rapid removal of Co metal. An existing chemical mechanical polishing slurry for cobalt achieves rapid removal of cobalt through the combined action of amino acids and other organic acids; and uses the synergistic action of azole corrosion inhibitors and ionic surfactant corrosion inhibitors to achieve low defects and a lower static corrosion rate of cobalt. However, after polishing Co with the above-mentioned polishing slurry, the Co metal surface has many defects and a high surface roughness.

[0038] The present application provides a polishing slurry, which can quickly remove Co during the chemical mechanical polishing process and has a high Co removal rate. At the same time, it has a low corrosion rate on the protective layer of the substrate, so that the protective layer has a high integrity.

[0039] A polishing slurry according to an embodiment of the present application includes a solvent and an abrasive, a stabilizer, a complexing agent and a corrosion inhibitor dispersed in the solvent. Among them, the mass proportion of the complexing agent in the polishing slurry may be 0.05% to 0.2%, and the mass proportion of the corrosion inhibitor in the polishing slurry may be 0.005% to 0.04%. In one embodiment, the polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent and 0.05-0.4 parts of corrosion inhibitor, and the remaining solvent. Among them, the weight parts of the abrasive are typically but not limited to 40 parts, 42 parts, 45 parts, 50 parts, 52 parts, 55 parts, 58 parts or 60 parts. The weight parts of the stabilizer are typically but not limited to 0.4 parts, 0.5 parts, and 0.6 parts. The weight percentage of the complexing agent is typically, but not limited to, 0.5, 0.8, 1, 1.2, 1.4, 1.5, 1.7, and 2. The weight percentage of the corrosion inhibitor is typically, but not limited to, 0.05, 0.08, 0.1, 0.12, 0.15, 0.17, 0.19, 0.2, 0.25, 0.3, 0.35, or 0.4.

[0040] In another embodiment, the polishing slurry may include a surfactant in addition to the above substances. The polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent and 0.05-0.4 parts of corrosion inhibitor and 0.01-0.03 parts of non-ionic surfactant, and the remaining solvent. The weight parts of non-ionic surfactant are typically but not limited to 0.01 parts, 0.015 parts, 0.02 parts, 0.025 parts, and 0.03 parts.

[0041] In another embodiment, the polishing slurry may further include a complexing agent. The polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent, 0.05-0.4 parts of corrosion inhibitor, 0.01-0.03 parts of nonionic surfactant, 0.03-0.06 parts of complexing agent and the remaining solvent. The weight parts of the complexing agent are typically but not limited to 0.03 parts, 0.04 parts, 0.05 parts, and 0.06 parts.

[0042] In another embodiment, the polishing slurry may further include a defoamer. The polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent, 0.05-0.4 parts of corrosion inhibitor, 0.01-0.03 parts of nonionic surfactant, 0.004-0.006 parts of defoamer, and the remaining solvent. The weight percentage of the defoamer is typically but not limited to 0.004 parts, 0.005 parts, and 0.006 parts.

[0043] In another embodiment, the polishing slurry may further include a bactericide. The polishing slurry includes the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent, 0.05-0.4 parts of corrosion inhibitor, 0.01-0.03 parts of nonionic surfactant, 0.004-0.006 parts of defoamer, 0.005-0.02 parts of bactericide, and the remaining solvent. The weight percentage of the bactericide is typically but not limited to 0.005 parts, 0.01 parts, 0.015 parts, and 0.02 parts.

[0044] In another embodiment, the polishing slurry may further include a pH adjuster, and the pH value of the polishing slurry is adjusted to between 2 and 12 by adding the pH adjuster.

[0045] In addition, an oxidant such as hydrogen peroxide may be selectively added. The polishing slurry comprises the following components based on 1000 parts by weight: 40-60 parts of abrasive, 0.4-0.6 parts of stabilizer, 0.5-2 parts of complexing agent, 0.05-0.4 parts of corrosion inhibitor, 0.01-0.03 parts of nonionic surfactant, 0.004-0.006 parts of defoamer, 0.01-0.03 parts of bactericide, 3-5 parts of oxidant, pH regulator and the rest of solvent. The weight percentage of the oxidant is typically but not limited to 3 parts, 3.5 parts, 4 parts, 4.5 parts and 5 parts.

[0046] The solvent may be an aqueous solvent, such as deionized water. Selecting deionized water as the solvent can reduce the introduction of impurity ions and protect the surface of Co from being corroded by the impurity ions.

[0047] The abrasive can be metal oxides such as silicon dioxide, zirconium oxide, aluminum oxide, etc.

[0048] The stabilizer can be selected from at least one of hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, hydroxyethyl methyl cellulose and benzyl cellulose. The stabilizer can play a dispersing role, and can make the abrasive dispersed evenly in the solvent to form a polishing slurry with uniform composition.

[0049] The complexing agent can be selected from amine compounds of 2-20 carbon atoms, and the amine compounds contain at least two amine groups. The number of amine groups can be 2-6. Exemplarily, the complexing agent can be selected from at least one of ethylenediamine, ethylenediaminetetraacetic acid, diethyltriaminepentaacetic acid, dipotassium ethylenediaminetetraacetic acid and disodium ethylenediaminetetraacetic acid. Preferably, the amine compound can be ethylenediaminetetraacetic acid. Ethylenediaminetetraacetic acid can be used as a complexing agent to achieve rapid removal of Co by utilizing its strong chelation with Co.

[0050] The corrosion inhibitor can be selected from organic phosphonic acid. Organic phosphonic acid can slow down the corrosion of polishing slurry, reduce its static corrosion rate and corrosion rate of protective layer, and ensure that polishing slurry has a low removal rate of oxide layer and protective layer. Organic phosphonic acid can be selected from phosphinocarboxylic acid, such as at least one of 2-phosphonobutane-1,2,4-tricarboxylic acid (2-phosphonobutane-1,2,4-tricarboxylic acid, PBTCA), hydroxyethylidene diphosphonic acid (1-hydroxy-1-phosphono-ethyl)-phosphonic acid, HEDP) and ethylenediaminetetramethylenephosphonic acid (ethylenediaminetetramethylenephosphonic acid, EDTMP). Phosphocarboxylic acid has the structural characteristics of both carboxylic acid and phosphonic acid, which can effectively ensure the surface quality of Co after polishing and reduce its surface roughness. Hydroxyethylidene diphosphonic acid can reduce the static corrosion rate of polishing slurry on Co, so that Co has suitable surface characteristics. Ethylene diamine tetramethylenephosphonic acid can help improve the removal rate of Co, and will not have too much influence on the removal rate of oxide layer and barrier layer.

[0051] The surfactant may be a nonionic surfactant. The nonionic surfactant is selected to avoid the introduction of impurity ions and protect the surface of Co from being contaminated. As an exemplary illustration, the surfactant in the embodiment of the present application may be one or any combination of two or more of emulsified silicone oil, high carbon alcohol fatty acid ester complex, polyoxyethylene, polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether, polyoxypropylene polyoxyethylene glycerol ether or polydimethylsiloxane.

[0052] The defoamer may be selected from at least one of a polydimethylsiloxane defoamer, an organosilicon defoamer and a polyether organosilicon defoamer.

[0053] The bactericide may be selected from at least one of dodecyldimethylbenzyl ammonium chloride, dodecyldimethylbenzyl ammonium bromide, tetradecyldimethylbenzyl ammonium chloride, polyquaternium salt, isothiazolinone, benzisothiazolinone and glutaraldehyde.

[0054] The pH regulator can be selected from at least one of potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonia, nitric acid, hydrochloric acid, HEDP, sulfuric acid and derivatives thereof. The pH regulator is used to adjust the pH value of the polishing slurry so that its pH value is in the range of 2-12. In one embodiment, the pH value of the polishing slurry is 7.5-9.

[0055] The polishing slurry of the embodiment of the present application can be used to achieve chemical mechanical polishing of a wafer of a chip containing a Co metal layer.

[0056] The polishing method of the substrate of the embodiment of the present application may include the following steps: applying the polishing slurry of the embodiment of the present application to the surface of the substrate, and driving the polishing object to polish the surface of the substrate covered with the polishing slurry; wherein the substrate includes a metal region, and the surface of the metal region contacts the polishing slurry. The metal of the metal region may be Co. The surface of the substrate layer may be provided with an oxide layer.

[0057] Figure 1 FIG. 1 is a schematic diagram of a chemical polishing process of a wafer containing a Co metal layer according to an embodiment of the present invention. Figure 1 As shown, after the Co metal layer 11 is deposited on the surface of the wafer and in the grooves, the wafer can be roughly polished by a mechanical polishing method, and then the wafer can be finely polished by the polishing slurry of the embodiment of the present application. Finally, the barrier layer 12 can be finely polished. Figure 1 The process shown is only a polishing process of a wafer in one embodiment, and the wafer may be polished specifically according to its structure and polishing part.

[0058] The polishing slurry of the present application will be further described in detail below in conjunction with specific embodiments.

[0059] Comparative Example 1

[0060] The comparative example is a polishing slurry, comprising the following raw material compositions by weight:

[0061] To 1885.92 g of deionized water, 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylene diamine tetraacetic acid (EDTA) complexing agent, 1 g of a polymer dispersant, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (20 wt%), and 10 g of an oxidant (hydrogen peroxide) were added in sequence, the mixture was thoroughly stirred, and the pH value was adjusted to 8.1 with aqueous ammonia.

[0062] Example 1

[0063] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0064] To 1885.72 g of deionized water, add in sequence 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 0.2 g of a PBTCA corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (20 wt %), and 10 g of an oxidant (hydrogen peroxide). Stir well and adjust the pH to 8.1 with aqueous ammonia.

[0065] Example 2

[0066] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0067] To 1885.72 g of deionized water, add in sequence 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 0.2 g of a HEDP corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (20 wt %), and 10 g of an oxidant (hydrogen peroxide). Stir well and adjust the pH value to 8.1 with aqueous ammonia.

[0068] Comparative Example 2

[0069] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0070] To 1885.72 g of deionized water, add in sequence 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 0.2 g of an EDTMPS corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (20 wt %), and 10 g of an oxidant (hydrogen peroxide). Stir well and adjust the pH value to 8.1 with aqueous ammonia.

[0071] Chemical mechanical polishing experiment: The machine model used in this polishing experiment is a general polishing machine, and the wafer used is a 2-inch wafer containing a cobalt layer, a titanium nitride layer and a silicon oxide dielectric layer. The above wafers were polished using the polishing slurries of Examples 1-3 and Comparative Example 1, respectively. The polishing parameters are polishing pressure: 2.5psi, polishing head speed: 87rpm, polishing disc speed: 93rpm, and polishing liquid flow rate: 125ml / min. The cobalt layer was polished for 30s, the titanium nitride layer was polished for 60s, and the silicon oxide dielectric layer was polished for 120s. After polishing, the wafer was cleaned with deionized water for 120s and dried with nitrogen.

[0072] After polishing, each group of experimental samples was tested to test the removal rate of Co and the removal rate of the oxide layer and nitride layer (TiN) in each group of wafers. The test results are listed in Table 1.

[0073] Table 1

[0074]

[0075] It can be seen from the relevant test data in Table 1 that when the polishing slurry corresponding to Examples 1-2 and Comparative Example 1 has a Co removal rate of Above, up to Above. Among them, when 0.01wt% of phosphine carboxylic acid (PBTCA) and 0.01wt% of HEDP are introduced into the ethylenediaminetetraacetic acid (EDTA) complexing agent system, the removal rate of Co shows a downward trend. When 0.01wt% of ethylenediaminetetramethylenephosphonic acid (EDTMPS) is added, the removal rate of Co will increase slightly. It can be observed in Table 1 that, compared with Co, the introduction of a small amount of organic phosphonic acid into the slurry has little effect on the removal rate of the oxide layer and the barrier layer material. Among them, the polishing slurry of each embodiment and comparative example also has a significant effect on the removal rate of the oxide layer. The removal rate of the nitride layer is about the same. A higher removal rate selectivity ratio can be obtained.

[0076] After chemical mechanical polishing, atomic force microscopy was used to observe and test the microscopic morphology changes of the samples before and after polishing corresponding to each embodiment and comparative example, and the test area range was 5*5 μm. Figure 2 These are micro-optical morphology images of samples of different embodiments and comparative examples after chemical mechanical polishing. Figure 2 (a) is the micro-light morphology image of the sample corresponding to Comparative Example 1, Figure 2 (b) is the micro-light morphology image of the sample corresponding to Example 1, Figure 2 (c) is the micro-light morphology image of the sample corresponding to Example 2. Figure 2 (d) is the low-light morphology image of the sample corresponding to Comparative Example 2.

[0077] like Figure 2 As shown, for the sample of comparative example 1, when the slurry does not contain organic phosphonic acid, the surface quality of Co after polishing is poor, and the surface roughness Ra is about 2.0nm. For the samples corresponding to Examples 1-2, when organic phosphonic acid is added to the slurry, the surface of Co after polishing is effectively improved, and Ra is about 1.0nm. However, the organic phosphonic acid ethylenediaminetetramethylenephosphonic acid (EDTMPS) in comparative example 2 has a slight effect on improving the surface quality of Co. Under the condition of 0.01% content, the improvement effect of phosphine carboxylic acid (PBTCA) and hydroxyethylidene diphosphonic acid (HEDP) on the surface quality of Co is not much different.

[0078] Comparative Example 3

[0079] The comparative example is a polishing slurry, comprising the following raw material compositions by weight:

[0080] Add 0.1 g of cellulose-based water-soluble polymer stabilizer, 0.2 g of ethylenediaminetetraacetic acid complexing agent, 0.1 g of polymer dispersant, 0.005 g of surfactant, 0.001 g of defoaming agent, 0.002 g of bactericide, and 1 g of oxidant (hydrogen peroxide) to 198.59 g of deionized water in sequence, stir well, and adjust the pH value to 8.1 with ammonia water.

[0081] Example 4

[0082] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0083] In 198.57 g of deionized water, add 0.1 g of cellulose water-soluble polymer stabilizer, 0.2 g of ethylenediaminetetraacetic acid complexing agent, 0.1 g of polymer dispersant, 0.02 g of PBTCA corrosion inhibitor, 0.005 g of surfactant, 0.001 g of defoaming agent, 0.002 g of bactericide, and 1 g of oxidant (hydrogen peroxide) in sequence, stir well, and adjust the pH value to 8.1 with ammonia water.

[0084] Example 5

[0085] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0086] In 198.57 g of deionized water, add 0.1 g of cellulose-based water-soluble polymer stabilizer, 0.2 g of ethylenediaminetetraacetic acid complexing agent, 0.1 g of polymer dispersant, 0.02 g of HEDP corrosion inhibitor, 0.005 g of surfactant, 0.001 g of defoaming agent, 0.002 g of bactericide, and 1 g of oxidant (hydrogen peroxide) in sequence, stir well, and adjust the pH value to 8.1 with ammonia water.

[0087] Comparative Example 4

[0088] The comparative example is a polishing slurry, comprising the following raw material compositions by weight:

[0089] In 198.57 g of deionized water, add 0.1 g of cellulose-based water-soluble polymer stabilizer, 0.2 g of ethylenediaminetetraacetic acid complexing agent, 0.1 g of polymer dispersant, 0.02 g of EDTMPS corrosion inhibitor, 0.005 g of surfactant, 0.001 g of defoaming agent, 0.002 g of bactericide, and 1 g of oxidant (hydrogen peroxide) in sequence, stir well, and adjust the pH value to 8.1 with ammonia water.

[0090] Static corrosion rate experiment: The wafer used in this experiment is a 2-inch cobalt wafer, and the test equipment used is a four-probe film thickness measuring instrument. The cobalt wafers treated with acid for 60 seconds were immersed in Examples 4-6 and Comparative Example 2 for 120 seconds, respectively, and then rinsed with deionized water for 120 seconds and dried with nitrogen. The corrosion thickness of the cobalt wafers of each group of samples was tested, and the corrosion rate was tested according to the corrosion thickness. The specific test results are listed in Table 2.

[0091] Table 2

[0092]

[0093] From the data in Table 2, it can be seen that the static corrosion rate of Co by the polishing slurries of Examples 3 and 4 is relatively low. The static corrosion rate of Co by the polishing slurry of Comparative Example 3 is higher. The above shows that when the corrosion inhibitor is selected from phosphine carboxylic acid and hydroxyethylene diphosphonic acid, the static corrosion rate of Co by the polishing slurry can be effectively reduced, and the excessive corrosion of Co by the polishing slurry can be prevented when Co is in a static state with the polishing slurry, thereby improving the surface quality of Co after polishing. In Comparative Example 4, when a small amount of EDTMPS is added to the solution, the static corrosion rate of Co is relatively high, and it can be placed The etching rate is significantly higher than that of the corresponding examples of phosphine carboxylic acid and hydroxyethylene diphosphonic acid, which is consistent with the CMP removal rate trend of Co.

[0094] Example 5

[0095] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0096] In 1885.72 g of deionized water, add 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 0.2 g of a phosphine carboxylic acid corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (mass content 20 wt%), and 10 g of an oxidant (hydrogen peroxide), stir well, and adjust the pH to 8.1 with aqueous ammonia.

[0097] Example 6

[0098] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0099] In 1885.32 g of deionized water, add 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 0.6 g of a phosphine carboxylic acid corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (mass content 20 wt%), and 10 g of an oxidant (hydrogen peroxide), stir well, and adjust the pH to 8.1 with aqueous ammonia.

[0100] Comparative Example 5

[0101] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0102] In 1884.92 g of deionized water, add 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 1 g of a phosphine carboxylic acid corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (mass content 20 wt%), and 10 g of an oxidant (hydrogen peroxide), stir well, and adjust the pH to 8.1 with aqueous ammonia.

[0103] Comparative Example 6

[0104] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0105] In 1884.52 g of deionized water, add 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 1.4 g of a phosphine carboxylic acid corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (mass content 20 wt%), and 10 g of an oxidant (hydrogen peroxide), stir well, and adjust the pH to 8.1 with aqueous ammonia.

[0106] Comparative Example 7

[0107] This embodiment is a polishing slurry, comprising the following raw material compositions by weight:

[0108] In 1883.92 g of deionized water, add 1 g of a cellulose-based water-soluble polymer stabilizer, 2 g of an ethylenediaminetetraacetic acid complexing agent, 1 g of a polymer dispersant, 2 g of a phosphine carboxylic acid corrosion inhibitor, 0.05 g of a surfactant, 0.01 g of a defoaming agent, 0.02 g of a bactericide, 100 g of colloidal silicon dioxide (mass content 20 wt%), and 10 g of an oxidant (hydrogen peroxide), stir well, and adjust the pH to 8.1 with aqueous ammonia.

[0109] Chemical mechanical polishing experiment: The machine model used in this polishing experiment is a general polishing machine, and the wafer used is a 2-inch wafer containing a cobalt layer, a titanium nitride layer and a silicon oxide dielectric layer. The above wafers were polished using the polishing slurries of Examples 1-3 and Comparative Example 1, respectively. The polishing parameters are polishing pressure: 2.5psi, polishing head speed: 87rpm, polishing disc speed: 93rpm, and polishing liquid flow rate: 125ml / min. The cobalt layer was polished for 30s, the titanium nitride layer was polished for 60s, and the silicon oxide dielectric layer was polished for 120s. After polishing, the wafer was cleaned with deionized water for 120s and dried with nitrogen.

[0110] After polishing, each group of experimental samples was tested to test the removal rate of Co and the removal rate of the oxide layer in each group of wafers. The test results are listed in Table 3.

[0111] Table 3

[0112]

[0113]

[0114] It can be seen from the relevant test data in Table 3 that the removal rate of Co by the polishing slurries of Examples 5 and 6 is The polishing slurries of Comparative Examples 5-7 have a Co removal rate of It is shown below that when the amount of phosphinocarboxylic acid added to the polishing slurry exceeds 0.04%, it has a significant effect on reducing the removal rate of Co. Therefore, in the polishing slurry of the embodiment of the present application, the amount of phosphinocarboxylic acid added is controlled within 0.04%.

[0115] Figure 3 The effect of different concentrations (0.01wt.%, 0.03wt.%, 0.05wt.%, 0.07wt.%, 0.1wt.%) of PBTCA on the Co removal rate. Figure 4 The effects of different concentrations (0.01wt.%, 0.03wt.%, 0.05wt.%, 0.07wt.%, 0.1wt.%) of PBTCA on the removal rates of TiN and oxide layer. Figure 5 The effect of different concentrations (0.01wt.%, 0.03wt.%, 0.05wt.%, 0.07wt.%, 0.1wt.%) of PBTCA on the Co / oxide layer removal rate selectivity. Figure 3 It can be seen that with the increase of PBTCA content in the slurry, the material removal rate of Co gradually decreases. When the content of PBTCA in the slurry increases to 0.1wt.%, the removal rate of Co changes from Down to Depend on Figure 4 It can be seen that the change of PBTCA content has no obvious effect on the removal rate of TiN and oxide layer. The removal rate of the oxide layer fluctuates around Fluctuating left and right. Figure 5 It can be seen that there is a certain difference in the Co / oxide layer removal rate selectivity of the slurry in each embodiment. Among them, with the increase of PBTCA content, the Co / oxide layer removal rate selectivity of the slurry will show a trend of first increasing and then decreasing, and when the PBTCA content exceeds 0.03%, the Co / oxide layer removal rate selectivity decreases rapidly.

[0116] Figure 6 The effect of different concentrations (0%, 0.03wt.%, 0.1wt.%) of PBTCA on the surface quality of Co after polishing. Figure 6(a) is the micro-light morphology image of the sample corresponding to Comparative Example 1, Figure 6 (b) is the micro-light morphology image of the sample corresponding to Example 6, Figure 6 (c) is the micro-light morphology image of the sample corresponding to Comparative Example 7. Figure 6 It can be seen that the addition of PBTCA can effectively protect the Co surface. When the slurry does not contain PBTCA, the Ra value of the Co surface is about 2.0nm. With the increase of PBTCA content, the surface quality of Co always maintains a relatively stable state, and the Ra value is about 1.0nm.

[0117] Figure 7 The effects of different concentrations (0%, 0.03wt.%) of PBTCA on the surfaces of TiN and Oxide are shown in Figure 2. Figure 7 (a) is a micro-light morphology image of the oxide layer of the sample corresponding to Comparative Example 1, Figure 7 (b) is a micro-light morphology image of the oxide layer of the sample corresponding to Example 6, Figure 7 (c) is the micro-light morphology of TiN of the sample corresponding to Comparative Example 1, Figure 7 (d) is the micro-light morphology of TiN of the sample corresponding to Example 6. Figure 7 It can be seen that the surface roughness is maintained within 0.1 nm. This is mainly because the removal amount of TiN and Oxide by the slurry is low, and PBTCA has no negative impact on the surface quality of TiN and Oxide.

[0118] The pattern wafer (with grooves arranged at intervals) and the Co-coated wafer were chemically mechanically polished using the slurries of Comparative Example 1 and Example 8, respectively, and the two types of wafers were tested by a step profiler and a laser confocal microscope.

[0119] Step meter test: The wafer used is a 2-inch pattern wafer, and the test line widths are 50*50um and 10*10um respectively. For example, 50*50um means that the plane width is 50um, the groove width is 50um, and the plane and the groove are arranged alternately. The above pattern wafer is polished using the polishing liquid of comparative example 1 and the polishing liquid of embodiment 6 respectively. After polishing, the surface morphology of the wafer is tested using a step meter to detect the height difference between the steps in the wafer thickness direction. The test results are shown in Figure 1. Figure 8 and Fig. 9 shown.

[0120] Figure 8 and Fig. 9 The relationship between the step change of different line widths after chemical mechanical polishing and PBTCA. According to the different line widths, the step profiler and atomic force microscope are used for testing. Figure 8 and Fig. 9It can be seen that when the line width is large, a large step difference is likely to be generated. The height difference of the step surface is significantly reduced when the polishing liquid of the embodiment of the present application is used to obtain the polishing surface. Figure 8 Taking the results shown in the figure as an example, in the 50 / 50um step pattern, the height difference between the steps after polishing is The polishing liquid of the present application embodiment can reduce the height difference to about In the 10 / 10um step pattern, the height difference between the steps after polishing is about The polishing liquid of the present application embodiment can reduce the height difference to about Likewise, Fig. 9 As shown, at the line width of 2 / 2um, after adding PBTCA, the step height is significantly controlled.

[0121] Laser confocal microscope test: The wafer used is a 2-inch cobalt-coated wafer, the magnification is 20 times, and the scanning test range is 644*644um. Fig.10 This is the surface morphology of the cobalt-coated film after polishing under a laser confocal microscope. Fig.10 As shown in the figure, when there is no PBTCA in the slurry, circular corrosion defects will appear on the surface of Co wafer under 20 times magnification. After adding PBTCA, the surface macro defects of Co are significantly controlled, and similar circular corrosion will no longer appear.

[0122] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A polishing slurry, characterized in that: It includes a solvent and an abrasive, a stabilizer, a complexing agent and a corrosion inhibitor dispersed in the solvent; The complexing agent is an amine compound with C2-C20, the amine compound contains at least two amine groups, and the mass proportion of the complexing agent in the polishing slurry is 0.05% to 0.2%; The corrosion inhibitor is an organic phosphonic acid, and the organic phosphonic acid is selected from at least one of phosphine carboxylic acid and hydroxyethylene diphosphonic acid; the mass proportion of the corrosion inhibitor in the polishing slurry is 0.005% to 0.04%.

2. The polishing slurry according to claim 1, characterized in that The amine compound is selected from at least one of ethylenediamine, ethylenediaminetetraacetic acid, diethyltriaminepentaacetic acid, dipotassium ethylenediaminetetraacetate and disodium ethylenediaminetetraacetate.

3. The polishing slurry according to claim 2, characterized in that The complexing agent is ethylenediaminetetraacetic acid, and the organic phosphonic acid is phosphinocarboxylic acid.

4. The polishing slurry according to claim 2, characterized in that The complexing agent is ethylenediaminetetraacetic acid, and the organic phosphonic acid is hydroxyethylidene diphosphonic acid.

5. The polishing slurry according to any one of claims 1 to 4, characterized in that: The polishing slurry also includes a surfactant, which is a nonionic surfactant.

6. The polishing slurry according to claim 5, characterized in that The nonionic surfactant is selected from at least one of emulsified silicone oil, high carbon alcohol fatty acid ester complex, polyoxyethylene, polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether, polyoxypropylene polyoxyethylene glycerol ether and polydimethylsiloxane.

7. The polishing slurry according to any one of claims 1 to 6, characterized in that: The polishing slurry also includes at least one of a complexing agent, a defoaming agent, a bactericide and a pH regulator.

8. The polishing slurry according to claim 7, characterized in that The defoamer is selected from at least one of a polydimethylsiloxane defoamer, an organosilicon defoamer and a polyether organosilicon defoamer; The bactericide is selected from at least one of dodecyldimethylbenzyl ammonium chloride, dodecyldimethylbenzyl ammonium bromide, tetradecyldimethylbenzyl ammonium chloride, polyquaternium salt, isothiazolinone, benzisothiazolinone and glutaraldehyde; The pH regulator is selected from at least one of potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonia water, nitric acid, hydrochloric acid, HEDP, sulfuric acid and derivatives thereof.

9. The polishing slurry according to any one of claims 1 to 8, characterized in that: The stabilizer is selected from at least one of hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, hydroxyethyl methyl cellulose and benzyl cellulose.

10. A method for polishing a substrate, characterized in that: include: Apply the polishing slurry described in any one of claims 1 to 9 to the surface of the substrate, and drive the polishing object to polish the surface of the substrate covered with the polishing slurry; wherein the substrate includes a metal area, the surface of the metal area is in contact with the polishing slurry, and the metal in the metal area is Co.

Citation Information

Cited By

  • Cleaning composition and application thereof, leveling process and electronic device

    CN121610318A